Florida's Environment - Central West Region - Martin B. Main; Ginger M. Allen (EDIS)
The Florida Environment series, by Martin B. Main and Ginger M. Allen is published by the UF Department of Wildlife Ecology and Conservation, July 2007. Revised October 2007.